PERAN MODAL SOSIAL PADA BURUH GENDONG DENGAN PEDAGANG DAN PEMBELI DI SUB TERMINAL AGRIBISNIS JETIS BANDUNGAN - Manutede, Dear Silvia C. H; Suwartiningsih, Sri; Utomo, Alvianto W (KRITIS, 2019)
Establishment Jetis sub terminal agribusiness in the region of Bandungan as a vegetable center market is the solution to increase availability of food in sufficient quantity and quality at affordable prices and distribution by society. On the other hand it opens new jobs that workers carrying. Workers carrying also referred to as porters and manol. This study aims to identify and describe the role of social capital on the workers carrying with sellers and buyers in the sub terminal agribusiness Jetis, Bandungan Semarang regency. This type of research is qualitative with a constructivist approach, which began November 2016-February 2017 on the workers carrying / manol in Jetis sub terminal agribusiness, Bandungan. Data collected through observation and interviews. The results of this study indicate social capital as a means of supporting the success of the progress of the sub terminal agribusiness Jetis. The existence of strong social capital role in the sustainability of economic enterprises and also in employment any market participants. Research shows that their trust in the form of mutual trust, honesty, openness and helpfulness. Then forms the norm that happens is to be professional and responsible job. Furthermore, the network manifest in the form of kinship and were both looking for life.